Rapid thermal annealing for ultra-shallow junction in deep submicron CMOS integrated circuits - Qin, Fei Tao (2009)
In this MSC dissertation, the focus of the study has been on the effect of critical parameters of rapid thermal anneal on shallow implants for ultra-shallow junction formation. Spike anneal was found to be more effective than soak anneal for ultra-shallow function formation.